Cleavage of C–N bonds in carbon fiber/epoxy resin composites. Issue 4 (2nd March 2015) - Deng, Tiansheng; Liu, Ying; Cui, Xiaojing; Yang, Yongxing; Jia, Shiyu; Wang, Yingxiong; Lu, Chunxiang; Li, Debao; Cai, Rong; Hou, Xianglin
Abstract : ZnCl2 enables the effective recovery of carbon fiber and epoxy resin from their waste composites by cleaving C–N bonds. Abstract : The incompletely coordinated zinc ions in water enable the cleavage of R2C(secondary carbon)–N bonds without breaking the C–O (aromatic ether) and C–C bonds in carbon fiber/epoxy resin composites. This selective cleavage of C–N bonds favors the recovery of valuable carbon fiber and the basic carbon unit of epoxy resin from their waste composites.